Impact of cathode slot on current distribution in cathode carbon of an aluminum electrolyticl cell - J. G. He; W. J. Tao; Y. Li; G. Z. Dong; X. X. Cui (Metalurgija, 2022)
The current distribution in a fresh aluminum electrolytic cell with slotted carbons is investigated by the Finite Element Method (FEM). The effects of the length of slots, la and lc on current distribution were also determined. The maximum local current density and its position do not change with an increase in lc (0 ≤ lc ≤ 200 mm) for a 400 mm slot located 150 mm from the upper surface of the cathode carbon. However, the maximum current density shifts towards the cell center with increasing slot lengths. Current distribution control thus plays a role in optimizing the cathode slot length.